The Effect of an Educational Approach According to Kolb's Theory on Developing Motor Coordination and Teaching Students the Skills of the Smash and Block Wall - Sakhi, Rouaa Abdullah (Indonesian Journal Publisher, 2025)
This research aims to identify the impact of an educational approach based on Kolb's theory of experiential learning on developing motor coordination and learning the skills of the smash and block among students in the targeted academic year. Kolb's theory is a modern educational theory that emphasizes that learning is an ongoing process based on direct experience, reflection, conceptualization, and active experimentation, which enables students to participate and be active participants in the learning process. The research problem is that traditional teaching methods in the field of physical education may not take into account individual differences among students and do not provide them with sufficient opportunities for practical experimentation and analysis. This weakens their ability to acquire basic skills in sports, especially volleyball, which requires a high level of motor coordination and precision in performance. The research also aims to develop an educational approach based on Kolb's theory, identify the extent of this approach's impact on developing motor coordination among students, and measure the approach's impact on learning the skills of the smash and block compared to traditional methods. The importance of this research lies in its aim to introduce a modern educational approach to physical education teaching, one that helps connect practical and theoretical aspects and enhances student participation in building their motor skills, thus contributing to improved learning of complex volleyball skills. The researcher relied on designing an educational approach consistent with Kolb's four stages of theory (concrete experience, observation and reflection, conceptual abstraction, and active experimentation) and applying it to a sample of students.